VEEP. The complete fifth season [videorecording (DVD)]. - Louis-Dreyfus, Julia; Chlumsky, Anna; Walsh, Matt, 1964- (Home Box Office, 2017)
The showfollows Meyer and her staff as they attempt to make their mark and leave a lasting legacy, without getting tripped up in the day-to-day political games that define Washington.